Influence of Metallic Particles on Properties of Aluminium Composites through Taguchi Technique - B. Venkatesh; Anantha Raman Lakshmipathi; T. Prakash; Pothamsetty Kasi V. Rao; Rajesh Verma; N. Nagabhooshanam; Simon Yishak (Advances in Materials Science and Engineering, 2023)
In this work, aluminium composites have been evaluated in terms of their characteristics and behaviour. Stirring metallics and a specific quantity of ceramic-derived silicon nitride resulted in AA6061 composites (Si3N4). The mechanical, corrosion, and tribological properties of composites were investigated. Tensile, corrosion, and hardness characteristics have been improved in composites with a constant weight percent of ceramic and advanced metallic fortification. The improved hardness of the composite has decreased wear and friction. Furthermore, by using ceramic strengthening with the metal, the impact strength of the composites was condensed. In addition to the research, the design of experiments method was used to optimize the important wear test elements such as reinforcement %, applied stress, sliding distance, and speed. Analysis of variance was used to find the most significant testing features and its interface with wear performance and the friction coefficient of the composite specimen.